2022
DOI: 10.1002/ppap.202200192
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulations of reactive neutral chemistry in an argon‐methane plasma

Abstract: Molecular dynamics simulations are performed to study the reactions in the volume of a low-pressure methane plasma diluted in argon. In the first step, a 1D fluid model is used to determine the initial molar fractions of initial species. The obtained composition thus becomes the input for the reactive molecular dynamics simulations. The study is carried out at 300, 400, 500, and 1000 K. Increasing the temperature increases the range of different molecules formed. The time evolution of C 2 H and CH 3 and the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 74 publications
(153 reference statements)
0
5
0
Order By: Relevance
“…Moreover, species such as C 4 H 2 , C 4 H 3 , and C 6 H 3 are widely known in hydrocarbon plasmas for contributing to the growth of films and large molecules. [13,17,18,73] In a previous study, [30] their importance, as well as the one of C 6 H 4 , was reported for the growth of large molecules in the volume phase. This means that the amount of reactive and nonreactive volatile products is significant and therefore cannot be neglected.…”
Section: S γ βmentioning
confidence: 90%
See 2 more Smart Citations
“…Moreover, species such as C 4 H 2 , C 4 H 3 , and C 6 H 3 are widely known in hydrocarbon plasmas for contributing to the growth of films and large molecules. [13,17,18,73] In a previous study, [30] their importance, as well as the one of C 6 H 4 , was reported for the growth of large molecules in the volume phase. This means that the amount of reactive and nonreactive volatile products is significant and therefore cannot be neglected.…”
Section: S γ βmentioning
confidence: 90%
“…Note: Argon is not included in our simulations. [30] F I G U R E 1 (a) Stainless steel slab mimicking pristine electrodes. It is composed of 67% Fe (silver color), 17% Cr (ocher color), 14% Ni (ice blue color), and 2% Mo (tan color).…”
Section: Model For the Calculation Of Surface Loss Probabilities Duri...mentioning
confidence: 99%
See 1 more Smart Citation
“…[ 69 ] Molecular dynamics simulations have also pointed out the important role of ● C 2 H radicals in methane plasmas. [ 70 ]…”
Section: Applicability Of the Arrhenius‐like Approachmentioning
confidence: 99%
“…[69] Molecular dynamics simulations have also pointed out the important role of • C 2 H radicals in methane plasmas. [70] From the above assessment, mainly C 2 H 2 and C 2 H 4 are well-suited polymerizable monomers used, for example, to deposit hard coatings or diffusion-controlling layers. [71][72][73] However, they do not bear interesting functionalities, which is why they are also mixed with nonpolymerizable gases such as N 2 , NH 3 , CO 2 , CO, H 2 O, O 2 , and so on, to incorporate functional groups in a cross-linked hydrocarbon matrix.…”
Section: Plasma Polymerizationmentioning
confidence: 99%